THE DIFFERENCE OF PERCEPTIONS AMONG ACCOUNTING STUDENTS IN TANJUNGPURA UNIVERSITY TOWARDS ACCOUNTANT PROFESSION ON REGULAR, NON-REGULAR, AND INTERNATIONAL FIRST UNDERGRADUATED PROGRAMS - B41108025, Auliah Akbar Rhamadhana aulia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
ABSTRACTÂ This research is conducted to identify the differences of perception towards accountant profession among accounting students in Tanjungpura University, specifically between their enrolled years and their programs. The samples students are from the year 2012, 2013, and 2014 if sorted by their enrolled year, and from regular, non-regular, and international class if sorted by their programs. This research uses Paired Sample t-Test to identify their difference of perception.The results of the tests imply that their perception did differs, but the differences varies. In regular program, the 2014 studentsâ€™ perception towards â€œaccountant as a professionâ€ is higher than their 2012 and 2013 seniors. In non-regular program, the 2014 studentâ€™s perception towards â€œaccounting as a group activityâ€ is higher than their 2012 seniors. Among the 2013 students, international students have higher perception towards â€œaccounting as a scienceâ€ than their non-regular counterpart. Among 2014 students, regular students have higher perception towards â€œaccountant as a professionâ€ than their non-regular counterpart. Meanwhile, the test in international and 2012 students didnâ€™t imply any significant differences.Â Keywords : perception towards accountant profession, studentsâ€™ perceptionÂ